Clinical Patterns of Uveitis in a Tertiary Center in North China. (24th August 2017) - Gao, Fei; Zhao, Chan; Cheng, Gangwei; Pei, Minghang; Liu, Xinshu; Wang, Min; Jia, Shanshan; Zhang, Meifen
ABSTRACT: Purpose : To analyze the spectrum of uveitis at a tertiary hospital in northern China. Methods : This study is a retrospective study from June 2014 to February 2015. A total of 606 consecutive patients with uveitis were screened for etiologies and classified according to the anatomic sites of inflammation. Results : The mean age at presentation was 33.8 ± 15.5 years old. Males and females were almost equally affected. Panuveitis was the most common anatomic diagnosis, followed by anterior, posterior, and intermediate uveitis. VKH syndrome, Behçet disease and idiopathic anterior uveitis were the most common uveitis entities. Ocular complications were detected in 441 patients. Conclusions : More than half of the patients with uveitis from northern China had an identifiable cause or was diagnosed as a specific disease entity with VKH and BD among the major etiologies. Cataract, steroid-induced ocular hypertension and macular edema were the leading complications.